Influence of Na adsorption on the quantum conductance and metal-insulator transition of the In-Si(111)(4×1)–(8×2) nanowire array - Schmidt, Wolf Gero; Babilon, M.; Thierfelder, C.; Sanna, S.; Wippermann, S. (Physical Review B)

Group-VII point defects in ZnSe - dos Santos, L. S.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Band offsets in cubic GaN/AlN superlattices - Mietze, C.; Landmann, M.; Rauls, E.; Machhadani, H.; Sakr, S.; Tchernycheva, M.; Julien, F. H.; Schmidt, Wolf Gero; Lischka, K.; As, Donat Josef (Physical Review B)

Asymmetric saddling of single porphyrin molecules on Au(111) - Müllegger, S.; Rashidi, M.; Lengauer, T.; Rauls, E.; Schmidt, Wolf Gero; Knör, G.; Schöfberger, W.; Koch, R. (Physical Review B)

Combined ab initio and classical potential simulation study on silicon carbide precipitation in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, J. K. N.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Barium titanate ground- and excited-state properties from first-principles calculations - Sanna, S.; Thierfelder, C.; Wippermann, S.; Sinha, T. P.; Schmidt, Wolf Gero (Physical Review B)

Electron g-factor anisotropy in symmetric (110)-oriented GaAs quantum wells - Hübner, J.; Kunz, S.; Oertel, S.; Schuh, D.; Pochwała, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten; Oestreich, M. (Physical Review B)
We demonstrate by spin quantum beat spectroscopy that in undoped symmetric (110)-oriented GaAs/AlGaAs single quantum wells, even a symmetric spatial envelope wave function gives rise to an asymmetric in-plane electron Land´e g-factor. The anisotropy is neither a direct consequence of the asymmetric in-plane Dresselhaus splitting nor a direct consequence of the asymmetric Zeeman splitting of the hole bands, but rather it is a pure higher-order effect that exists as well for diamond-type lattices. The measurements for various well widths are very well described within 14 × 14 band k·p theory and illustrate that the electron spin is an excellent meter variable for mapping out the internal—otherwise hidden—symmetries in two-dimensional systems. Fourth-order perturbation theory yields an analytical expression for the strength of the g-factor anisotropy, providing a qualitative understanding of the observed effects.
Keywords: tet_topic_qw

Dirac point and edge states in a microwave realization of tight-binding graphene-like structures - Kuhl, U.; Barkhofen, Sonja; Tudorovskiy, T.; Stöckmann, H.-J.; Hossain, T.; de Forges de Parny, L.; Mortessagne, F. (Physical Review B)

Spin dynamics of electrons and holes inInGaAs/GaAsquantum wells at millikelvin temperatures - Fokina, L. V.; Yugova, I. A.; Yakovlev, D. R.; Glazov, M. M.; Akimov, I. A.; Greilich, A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Control of the transmission phase in an asymmetric four-terminal Aharonov-Bohm interferometer - Buchholz, Sven S.; Fischer, Saskia F.; Kunze, Ulrich; Bell, Matthew; Reuter, Dirk; Wieck, Andreas D. (Physical Review B)

Phase shifts and phaseπjumps in four-terminal waveguide Aharonov-Bohm interferometers - Kreisbeck, Christoph; Kramer, Tobias; Buchholz, Sven S.; Fischer, Saskia F.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D. (Physical Review B)

Theory of phonon-mediated relaxation in doped quantum dot molecules - Grodecka-Grad, A.; Förstner, Jens (Physical Review B)
A quantum dot molecule doped with a single electron in the presence of diagonal and off-diagonal carrierphonon couplings is studied by means of a nonperturbative quantum kinetic theory. The interaction with acoustic phonons by deformation potential and piezoelectric coupling is taken into account. We show that the phonon-mediated relaxation is fast on a picosecond time scale and is dominated by the usually neglected off-diagonal coupling to the lattice degrees of freedom leading to phonon-assisted electron tunneling. We show that in the parameter regime of current electrical and optical experiments, the microscopic non-Markovian theory has to be employed.
Keywords: tet_topic_qd

Reentrant superconductivity in superconductor/ferromagnetic-alloy bilayers - Zdravkov, V. I.; Kehrle, J.; Obermeier, G.; Gsell, S.; Schreck, M.; Müller, C.; Krug von Nidda, H.-A.; Lindner, Jörg; Moosburger-Will, J.; Nold, E.; Morari, R.; Ryazanov, V. V.; et al. (Physical Review B)
We studied the Fulde-Ferrell-Larkin-Ovchinnikov-type state established due to the proximity effect in superconducting Nb/Cu_41Ni_59 bilayers. Using a special wedge-type deposition technique, series of 20–35 samples could be fabricated by magnetron sputtering during one run. The layer thickness of only a few nanometers, the composition of the alloy, and the quality of interfaces were controlled by Rutherford backscattering spectrometry, high-resolution transmission electron microscopy, and Auger spectroscopy. The magnetic properties of the ferromagnetic alloy layer were characterized with superconducting quantum interference device magnetometry. These studies yield precise information about the thickness and demonstrate the homogeneity of the alloy composition and magnetic properties along the sample series. The dependencies of the critical temperature on the Nb and Cu41Ni59 layer thickness, T_c(d_S) and T_c(d_F), were investigated for constant thickness d_F of the magnetic alloy layer and d_S of the superconducting layer, respectively. All types of nonmonotonic behaviors of T_c versus d_F predicted by the theory could be realized experimentally, from reentrant superconducting behavior with a broad extinction region to a slight suppression of superconductivity with a shallow minimum. Even a double extinction of superconductivity was observed, giving evidence for the multiple reentrant behavior predicted by theory. All critical temperature curves were fitted with suitable sets of parameters. Then, T_c(d_F) diagrams of a hypothetical ferromagnet/superconductor/ferromagnet spin-switch core structure were calculated using these parameters. Finally, superconducting spin-switch fabrication issues are discussed in detail in view of the achieved results.

Defects in carbon implanted silicon calculated by classical potentials and first-principles methods - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, Jörg; Schmidt, W. G.; Rauls, E. (Physical Review B)
A comparative theoretical investigation of carbon interstitials in silicon is presented. Calculations using classical potentials are compared to first-principles density-functional theory calculations of the geometries, formation, and activation energies of the carbon dumbbell interstitial, showing the importance of a quantummechanical description of this system. In contrast to previous studies, the present first-principles calculations of the interstitial carbon migration path yield an activation energy that excellently matches the experiment. The bond-centered interstitial configuration shows a net magnetization of two electrons, illustrating the need for spin-polarized calculations.

Dynamics of photoexcitation and stimulated optical emission in conjugated polymers: A multiscale quantum-chemistry and Maxwell-Bloch-equations approach - Schumacher, Stefan; Galbraith, Ian; Ruseckas, Arvydas; Turnbull, Graham A.; Samuel, Ifor D. W. (Physical Review B)

Manganese-hydrogen complexes inGa1−xMnxN - Bihler, C.; Gerstmann, Uwe; Hoeb, M.; Graf, T.; Gjukic, M.; Schmidt, Wolf Gero; Stutzmann, M.; Brandt, M. S. (Physical Review B)

Defects in carbon implanted silicon calculated by classical potentials and first-principles methods - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, J. K. N.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

First-principles study of water adsorption and a high-density interfacial ice structure on(1×1)-O/Rh(111) - Thierfelder, C.; Schmidt, Wolf Gero (Physical Review B)

Lithium niobateX-cut,Y-cut, andZ-cut surfaces fromab initiotheory - Sanna, Simone; Schmidt, Wolf Gero (Physical Review B)

Chemical reactivity on surfaces: Modeling the imide synthesis from DATP and PTCDA on Au(111) - Rauls, E.; Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)